Reflective equilibria in metrology?: a case study on the current reform of the international system of units - Schlaudt, Oliver (Analyse & Kritik, 2016)
In this paper I propose to read the history of systems of units, and in particular the current reform of the International System of Units (SI), understood as a set of measuring norms, in the light of reflective equilibria. The idea is that the model of reflective equilibria actually applies to processes which can be empirically observed or studied. This can help us to understand the nature of normativity and to shed light on its relativity to, and dependence on, practice.
Online veröffentlicht: 22.11.2016
Gesehen am 21.10.2020